The concept of political struggle by Maurice Duverger in application to the novel "The Beautiful Knight" - Alifatul Hidayatin; Wildana Wargadinata; Faris Maturedy (Hijai - Journal on Arabic Language and Literature, 2023)
The purpose of this study is to describe the causes and effects of political conflict in al-Faris al-Jamil's novel based on Maurice Duverger's theory. This study uses descriptive qualitative research methods. The data in this study were obtained through the novel "al Faris al Jamil" by Ali Ahmad Baltsir. Data were collected by three techniques. Namely the listening technique and note-taking technique. The data that has been obtained must go through the validation stage. The validation process is carried out by increasing research persistence, triangulation and discussion with experts. The data analysis used by the researcher is the analysis of the Miles and Hubarman model. Namely, the presentation, reduction and formulation of data conclusions. The results of the study show that: First, the form of political conflict in this novel is the circulation of weapons, there are many wars and the use of political strategies. Second: Political conflict is caused by 2 factors: personal factors and group factors. Third: This social conflict can cause effects, both positive and negativeØ§Ù„Ù…Ù„Ø®ØµÙ‡Ø¯ÙØª Ù‡Ø°Ù‡ Ø§Ù„Ø¯Ø±Ø§Ø³Ø© Ø¥Ù„Ù‰ ÙˆØµÙ Ù…Ø§ ÙÙŠ Ø±ÙˆØ§ÙŠØ© Ø§Ù„ÙØ§Ø±Ø³ Ø§Ù„Ø¬Ù…ÙŠÙ„ Ù„Ø¹Ù„ÙŠ Ø£ØÙ…Ø¯ Ø¨Ø§ÙƒØ«ÙŠØ± Ù…Ù† Ø§Ù„ØµØ±Ø§Ø¹ Ø§Ù„Ø³ÙŠØ§Ø³ÙŠ. ÙˆØ§Ø¹ØªÙ…Ø¯ Ø§Ù„Ø¨Ø§ØØ«Ù†ÙˆÙ† ÙÙŠ Ø§Ù„Ù†Ø¸Ø± Ø¥Ù„Ù‰ ØµÙˆØ± Ø§Ù„ØµØ±Ø§Ø¹ Ø§Ù„Ø³ÙŠØ§Ø³ÙŠ ÙÙŠ Ù‡Ø°Ù‡ Ø§Ù„Ø±ÙˆØ§ÙŠØ© Ø¹Ù„Ù‰ Ù†Ø¸Ø±ÙŠØ© Ù…ÙˆØ±ÙŠØ³ Ø¯ÙˆÙÙŠØ±Ø¬ÙŠØ±. ÙˆØ¨Ø§Ù„ØªØ§Ù„ÙŠ Ø§Ø±ØªÙƒØ² Ø§Ù„Ø¨Ø§ØØ«ÙˆÙ† ÙÙŠ ÙˆØµÙ Ø§Ù„ØµØ±Ø§Ø¹ Ø§Ù„Ø³ÙŠØ§Ø³ÙŠ ÙˆÙƒÙ„ Ù…Ø§ ÙŠØªØ¹Ù„Ù‚ Ø¨Ù‡ Ù…Ù† Ø§Ù„Ø¹ÙˆØ§Ù…Ù„ ÙˆØ§Ù„Ø£Ø³Ø¨Ø§Ø¨. Ø£Ù…Ø§ Ù…Ù†Ù‡Ø¬ Ø§Ù„Ø¨ØØ« ÙØ§Ø®ØªØ§Ø± Ø§Ù„Ø¨Ø§ØØ«ÙˆÙ† Ù…Ù†Ù‡Ø¬ Ø§Ù„Ø¨ØØ« Ø§Ù„ÙƒÙŠÙÙŠ. ÙˆØ£Ù…Ø§ Ù…ØµØ§Ø¯Ø± Ø§Ù„Ø¨ÙŠØ§Ù†Ø§Øª ÙÙ‡Ùˆ Ø±ÙˆØ§ÙŠØ© "Ø§Ù„ÙØ§Ø±Ø³ Ø§Ù„Ø¬Ù…ÙŠÙ„" Ù„Ø¹Ù„ÙŠ Ø£ØÙ…Ø¯ Ø¨Ø§ÙƒØ«ÙŠØ± ÙØØ³Ø¨. ÙˆØ¬Ù…Ø¹ Ø§Ù„Ø¨Ø§ØØ«ÙˆÙ† Ø§Ù„Ø¨ÙŠØ§Ù†Ø§Øª Ù…Ù† Ø®Ù„Ø§Ù„ Ø«Ù„Ø§Ø« Ø®Ø·ÙˆØ§ØªØŒ ÙˆÙ‡ÙŠ Ø§Ù„Ù‚Ø±Ø§Ø¡Ø© ÙˆØªØ³Ø¬ÙŠÙ„ Ù…Ø§ Ù„Ù‡Ø§ ØªØ¹Ù„Ù‚ Ø¨Ø§Ù„Ù…ÙˆØ¶ÙˆØ¹ Ù…Ù† Ø§Ù„ØµØ±Ø§Ø¹ Ø§Ù„Ø³ÙŠØ§Ø³ÙŠ ÙˆØ§Ù„ØªØ±Ø¬Ù…Ø©. Ø«Ù… ØªÙ… ØµØ¯ÙŠÙ‚ Ø§Ù„Ø¨ÙŠØ§Ù†Ø§Øª Ø¨ÙˆØ§Ø³Ø·Ø© Ø²ÙŠØ§Ø¯Ø© Ø§Ù„Ù…Ø«Ø§Ø¨Ø±Ø© ÙˆØ§Ù„ØªØ«Ù„ÙŠØ« ÙˆØ§Ù„Ù…Ù†Ø§Ù‚Ø´Ø© Ù…Ø¹ Ø§Ù„Ø®Ø¨Ø±Ø§Ø¡. ÙˆØ£Ù…Ø§ ØªØÙ„ÙŠÙ„ Ø§Ù„Ø¨ÙŠØ§Ù†Ø§Øª ÙØªÙƒÙˆÙ† Ù…Ù† Ø«Ù„Ø§Ø« Ø®Ø·ÙˆØ§Øª ÙˆÙ‡ÙŠ Ø§Ù„ØªØ®ÙÙŠØ¶ ÙˆØ§Ù„Ø¹Ø±Ø¶ ÙˆØ§Ù„Ø§Ø³ØªÙ†ØªØ§Ø¬. ÙˆÙ„Ù‡Ø°Ù‡ Ø§Ù„Ø¯Ø±Ø§Ø³Ø© Ù†ØªØ§Ø¦Ø¬ Ù‡Ø§Ù…Ø© ØÙˆÙ„ Ø§Ù„ØµØ±Ø§Ø¹ Ø§Ù„Ø³ÙŠØ§Ø³ÙŠ ÙˆÙ‡ÙŠ Ø£ÙˆÙ„Ø§ØŒ Ø§Ù†ØªØ´Ø§Ø± Ø§Ù„Ø£Ø³Ù„ØØ© ÙˆØØ¯ÙˆØ« ÙƒØ«ÙŠØ± Ù…Ù† Ø§Ù„Ù…Ø¹Ø±ÙƒØ© ÙˆØ§Ø³ØªØ¹Ù…Ø§Ù„ Ø§Ø³ØªØ±Ø§ØªÙŠØ¬ÙŠØ© Ø§Ù„Ø³ÙŠØ§Ø³Ø©. Ø«Ø§Ù†ÙŠØ§ØŒ ØªØªÙØ±Ø¹ Ø§Ù„Ø£Ø³Ø¨Ø§Ø¨ Ø§Ù„Ù…Ø¤Ø¯ÙŠØ© Ø¥Ù„Ù‰ Ø§Ù„ØµØ±Ø§Ø¹ Ø§Ù„Ø³ÙŠØ§Ø³ÙŠ Ø¥Ù„Ù‰ ÙØ±Ø¹ÙŠÙ†: Ø§Ù„Ø£Ø³Ø¨Ø§Ø¨ Ø§Ù„ÙØ±Ø¯ÙŠØ© ÙˆØ§Ù„Ø£Ø³Ø¨Ø§Ø¨ Ø§Ù„Ø¬Ù…Ø§Ø¹ÙŠØ©. Ø«Ø§Ù„Ø«Ø§ØŒ ÙˆÙ„Ù„ØµØ±Ø§Ø¹ Ø§Ù„Ø³ÙŠØ§Ø³ÙŠ Ø¢Ø«Ø§Ø± Ø¥ÙŠØ¬Ø§Ø¨ÙŠØ© ÙƒØ§Ù†Øª Ø£Ù… Ø³Ù„Ø¨ÙŠØ©.Â ABSTRAKTujuan dari penelitian ini yaitu menggambarkan sebab dan pengaruh konflik politik novel al-Faris al-Jamil berdasarkan teori Maurice Duverger. Penelitian ini menggunakan metode penelitian kualitatif deskriptif. Data dalam penelitian ini diperoleh melalui novel â€œal Faris al Jamilâ€ karya Ali Ahmad Baltsir. Data dikumpulkan dengan tiga teknik. Yaitu teknik simak dan teknik catat. Data yang telah diperoleh harus melalui tahapanÂ  validasi. Proses validasi dilakukan dengan peningkatan ketekunan penelitian, triangulasi dan diskusi bersama para ahli. Analisis data yang digunakan oleh peneliti yaitu analisis model Miles dan Hubarman. Yaitu, penyajian, reduksi dan perumusan kesimpulan data. Hasil penelitian menunjukkan bahwa: Pertama, bentuk konflik politik dalam novel ini yaitu beredarnya senjata, banyak terjadi peperangan dan penggunaan strategi politik. Kedua: Konflik politik disebabkan karena 2 faktor: faktor pribadi dan faktor golongan. Ketiga: Konflik sosial ini dapat menyebabkan pengaruh, baik yang bersifat positif maupun negatif.